Learning Financial Literacy Through Savings Activities in Islamic Elementary Schools: Empirical Evidence at Islamic Elementary School - Hendri Hermawan Adinugraha; Irham Baihaqi Thoha; Haryanto Kanthi Widodo; Moh. Hamdi; Razie Bin Nasarruddin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2022)
Understanding and saving habits from an early age is the most important practice in the financial literacy of the Indonesian people, especially for children who are currently attending elementary school, including students of MI Al-Ustmani. The researcher used descriptive qualitative research. The research subjects used were students of MI Al-Ustmani. Data collection techniques in this study are interviews, observation, and documentation. Data analysis used in this research is data organization, data reading, describing data into code, classifying coding into themes, interpreting data, and presenting data. Researchers found empirical evidence that financial literacy learning at MI Al-Ustmani has been carried out through saving activities that are practiced by students every day. MI Al-Ustmani has included financial literacy both intra-curriculum and extra-extra-curriculum as well as direct practicum in the classroom. Learning financial literacy education through saving activities for MI Al-Ustmani students requires cooperation and synergy from various parties so that financial education is truly internalized in the mindset and can be manifested in the daily behavior of MI Al-Ustmani students.